2022
DOI: 10.36253/ijae-13035
|View full text |Cite
|
Sign up to set email alerts
|

The location of the mental foramen in relation to the biometrics of the lower dentition and mandibular arch: A cross-sectional study

Abstract: Purpose: To evaluate the position of the mental foramen among Malaysian Malays and Chinese based on the biometrics of the lower dentition and mandibular arch dimensions.  Materials and methods: The horizontal and vertical position of mental foramen in relation to the midline, roots of teeth, mesiodistal dimension of the anterior and posterior teeth, and the mandibular arch length and width were measured and evaluated in 65 Cone-Beam Computed Tomography scans.  Results: The location of mental forame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…However, after the emergence of micro-computed tomography (µCT), and the quantification of trabecular architecture by µCT yielded promising results, and its ability to attain resolutions up to 0.5 µm, it is currently tagged as a non-destructive gold standard [ 21 ]. Previous studies have validated CBCT to be used as an assessment tool to quantify trabecular microarchitecture [ 22 , 23 , 24 , 25 , 26 ]. The studies suggested that morphometric assessments by most CBCT machines and high-resolution multi-scanner computed tomography (MSCT) are reliable, though they over-estimated the trabecular microarchitecture the alveolar network remained the same between them and the reference gold standard (µCT) [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, after the emergence of micro-computed tomography (µCT), and the quantification of trabecular architecture by µCT yielded promising results, and its ability to attain resolutions up to 0.5 µm, it is currently tagged as a non-destructive gold standard [ 21 ]. Previous studies have validated CBCT to be used as an assessment tool to quantify trabecular microarchitecture [ 22 , 23 , 24 , 25 , 26 ]. The studies suggested that morphometric assessments by most CBCT machines and high-resolution multi-scanner computed tomography (MSCT) are reliable, though they over-estimated the trabecular microarchitecture the alveolar network remained the same between them and the reference gold standard (µCT) [ 27 ].…”
Section: Introductionmentioning
confidence: 99%